TACE Combined with Lenvatinib-PD-1 Versus TACE Monotherapy as Conversion Therapy Before Liver Resection in Unresectable Hepatocellular Carcinoma: A Retrospective, Propensity Score Matching Study - Lu C; Liu R; Zhang Y; Luo J; Luo C; Jiang Z; Huang M; Qiu C; Chen J (Journal of Hepatocellular Carcinoma)
Caiyun Lu,1,* Renming Liu,2,* Yanyang Zhang,1,* Junyang Luo,1 Cheng Luo,3 Zaibo Jiang,1 Mingsheng Huang,1 Chunhui Qiu,4 Junwei Chen1 1Department of Interventional Radiology, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China; 2Department of Pathology, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China; 3Department of General Medicine, The Third Affiliated Hospital of Sun Yat-sen University, Guangzhou, Guangdong, People’s Republic of China; 4Department of Hepatic Surgery, The Third Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chunhui Qiu, Department of Hepatic Surgery, The Third Affiliated Hospital of Sun Yat-Sen University, No. 600, Tianhe Road, Tianhe District, Guangzhou, Guangdong, People’s Republic of China, Email qiuchh@mail.sysu.edu.cn Junwei Chen, Department of Interventional Radiology, The Third Affiliated Hospital of Sun Yat-sen University, No. 600, Tianhe Road, Tianhe District, Guangzhou, Guangdong, People’s Republic of China, Email chenjw53@mail.sysu.edu.cnBackground: Transarterial chemoembolization (TACE) combined with Lenvatinib plus programmed death-1 inhibitor (PD-1 inhibitor) is recommended for unresectable hepatocellular carcinoma (uHCC), and it has increased the probability of successful conversion. Our aim was to compare the clinical benefits of TACE combined with Lenvatinib-PD-1 inhibitor versus TACE monotherapy as conversion therapy for patients with uHCC who subsequently underwent liver resection (LR).Materials and Methods: This retrospective study included 213 uHCC patients who underwent LR after receiving either TACE combined with Lenvatinib plus PD-1 inhibitor (combination group, n=109) or TACE monotherapy (monotherapy group, n=104). Propensity score matching was employed to minimize baseline confounding variables between cohorts. Tumor response, disease-free survival (DFS), overall survival (OS), and adverse events (AEs) were assessed between treatment arms.Results: Among 68 matched pairs of patients who underwent LR, only 1 patient developed small-for-size syndrome. The combination group demonstrated superior treatment responses compared with the monotherapy group, with a significantly higher objective response rate (92.65% vs 80.88%, p=0.043) and pathological complete response rate (36.76% vs 11.76%, p< 0.001). Furthermore, histopathological analyses revealed a lower incidence of microvascular invasion in the combination group compared with the monotherapy group (14.71% vs 29.41%, p=0.039). Survival analyses demonstrated significantly improved DFS (median not reached vs 20.0 months, p=0.002) and OS (median not reached for both, p=0.005) in the combination group. Multivariate Cox proportional hazards regression identified preoperative monotherapy as an independent adverse prognostic factor for both DFS (HR, 2.46) and OS (HR, 3.05). Although combination therapy showed superior therapeutic efficacy, it was linked to a significantly higher incidence of rash and hand-foot skin reactions.Conclusion: Compared to TACE monotherapy, TACE combined with Lenvatinib-PD-1 inhibitor as conversion therapy can improve long-term survival outcomes in patients with uHCC who undergo subsequent LR, with an acceptable safety profile. Keywords: hepatocellular carcinoma, conversion therapy, transarterial chemoembolization, Lenvatinib, programmed death-1 inhibitor